Jurassic – Cretaceous boundary record in Carpathian sedimentary sequences. (February 2021) - Michalík, Jozef; Grabowski, Jacek; Lintnerová, Otília; Reháková, Daniela; Kdýr, Šimon; Schnabl, Petr
Abstract: An integrated study of micro- and nannoplankton distribution, O and C isotopes and palaeomagnetic record of nine Carpathian sections provided a key interpretation tool to characterize the Jurassic–Cretaceous (J/K) boundary transition. Biostratigraphy supported by saccocomids, radiolarians, calpionellids, dinoflagellates and nannofossils helped to distinguish biostratigraphic zones which could have been correlated both with stable isotopes and with magnetostratigraphy. The Alpina Event (lorica size change) accompanied by Nannoconus wintereri and N . steinmannii minor FO's designates the J/K boundary. Sedimentary model in N Mediterranean Tethys margin consists of elevated blocks with slow (1–2 mm/ka) Rosso Ammonitico carbonate sedimentation separated by dysoxic depressions. Tectonic instability has been indicated by Upper Jurassic fluxoturbidites. Late early Tithonian (M21n to M20r) saccocomid abundance increases with positive δ 18 O isotope ratios, similar excursion between M20n and M19r accompanied late Tithonian crassicollarian boom. The δ 13 C variation (>0.2‰) confronted with microplankton quantity variations: positive excursion occurred both during early Tithonian Saccocoma sp., and during late Tithonian calpionellid and nannoconid blooms. Higher up in the Berriasian "Maiolica" sequence, lighter δ 13 C values prevailed. During late Tithonian (Praetintinnopsella-to earliest Crassicollaria zones; M20n1n to M19r), Saccocoma microfacies has been substituted by a calpionellid one. Reorganization of Tethyan oceanic currents during opening of the Hispanic corridor started planktonic carbonate particle „rain" resulting in the Maiolica facies dominance. Sedimentary rate raised ten times. Calpionella alpina lorica size change event was synchronneous with FO's of Nannoconus wintereri and N . steinmannii minor and with negative δ 18 O trend of latest Tithonian (Colomi Subzone) warming. Expressiveness of eccentricity and obliquity cycles indicates climatic optimum conditions.